The chupacabra ate the candelabra - Nobleman, Marc Tyler; Aranda, Ana (New York, NY : Nancy Paulsen Books, 2017)
It's common knowledge that goats are a chupacabra's favorite food! One night, tired of living in fear, Jayna, Bumsie and Pep whip out their trusty candelabra and head off to find the beast and scare it away before it can find them. Little do they know that candelabras are the chupacabra's third-favorite food -- and this one has quite the appetite. The goats are in for a big surprise!
Ages 5-8.
Accelerated Reader AR
Keywords: Chupacabras -- Juvenile fiction; Goats -- Juvenile fiction; Food habits -- Juvenile fiction; Chupacabras -- Fiction; Goats -- Fiction; Food habits -- Fiction; Humorous stories